Vulnerable personality profile in patients with chronic pain: relationship with coping, quality of life and adaptation to disease (2012)
In this study with a sample of chronic pain patient, personality profiles defined as the individual’s scores on all five dimensions (NEO-FFI) are used, to establish relations with coping, quality of life, and adaptation to disease. After a cluster analysis two groups have been obtained: the first one being a trend to intermediate scores in all five dimensions and characterized by moderate neuroticism, average extraversion, low openness, moderate agreeableness, and moderate conscientiousness, whereas the second one is characterized by traits of vulnerability determined by high neuroticism, low extraversion, low openness, moderate agreeableness and low conscientiousness. Significant univariate differences are seen between both groups in the use of coping strategies (CAD-R), quality of life (SF-36), and adaptation to disease (LI). In addition, multivariate differences are seen in coping and quality of life.